HCl treatment on micropore and mesopore structures of carbon cryogels from resorcinol and formaldehyde - Kraiwattanawong, Kriangsak; Tamon, Hajime; Praserthdam, Piyasan (My University, 2011)
The effect of HCl treatment on the porous properties of carbon cryogels synthesized from resorcinol and formaldehyde (RF) is investigated in this work. The treated and untreated carbon cryogels were analyzed with a nitrogen adsorption-desorption apparatus, scanning electron microscope (SEM) and high performance liquid chromatograph (HPLC). The results show that the HCl treatment can enlarge the micropore diameter which is advantageous to electric double layer capacitors, and can broaden the mesopore diameter, which is advantageous to mesoporous carbon supports of catalysts. The micropore volume, mesopore volume and weight loss of the carbon cryogel are not significantly changed by the HCl treatment. Moreover, SEM images and HPLC chromatograms support that the HCl treatment can promote the Ostwald ripening effect for RF carbon cryogels. © 2011 The Society of Chemical Engineers, Japan.
Keywords: Carbon Cryogel; Freeze Drying; HCl Treatment; Mesopore Structure; Porosity